2022
DOI: 10.1111/joim.13448
|View full text |Cite
|
Sign up to set email alerts
|

The role of environmental exposures and gene–environment interactions in the etiology of systemic lupus erythematous

Abstract: Systemic lupus erythematosus (SLE) is a complex, chronic autoimmune disease, whose etiology includes both genetic and environmental factors. Individual genetic risk factors likely only account for about one‐third of observed heritability among individuals with a family history of SLE. A large portion of the remaining risk may be attributable to environmental exposures and gene–environment interactions. This review focuses on SLE risk associated with environmental factors, ranging from chemical and physical env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 166 publications
0
34
1
Order By: Relevance
“…Previously, epidemiological studies showed that there was no significant association between alcohol consumption and SLE ( 110 , 162 166 ). However, in the last several decades, several studies have consistently suggested that moderate alcohol consumption was negatively associated with the risk of SLE, irrespective of the type of alcoholic beverage ( 3 , 112 , 115 , 167 , 168 ). A meta-analysis of six case-control studies and one cohort study published in 2008 revealed that moderate alcohol consumption likely has a protective effect against the development of SLE ( 169 ).…”
Section: Effects Of Cigarette Smoking and Consumption Of Alcohol And ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, epidemiological studies showed that there was no significant association between alcohol consumption and SLE ( 110 , 162 166 ). However, in the last several decades, several studies have consistently suggested that moderate alcohol consumption was negatively associated with the risk of SLE, irrespective of the type of alcoholic beverage ( 3 , 112 , 115 , 167 , 168 ). A meta-analysis of six case-control studies and one cohort study published in 2008 revealed that moderate alcohol consumption likely has a protective effect against the development of SLE ( 169 ).…”
Section: Effects Of Cigarette Smoking and Consumption Of Alcohol And ...mentioning
confidence: 99%
“…Recent research focused on cigarette smoking affecting clinical manifestations of patients with SLE has indicated that cigarette smoking was associated with photosensitivity, cutaneous damage, active SLE rash ( 124 127 ), higher SLE Disease Activity Index (SLEDAI) score ( 128 ), pleuritis, peritonitis, metabolic syndrome ( 129 ), neuropsychiatric symptoms ( 130 , 131 ), vascular necrosis ( 132 ), thrombotic events ( 133 136 ), cardiovascular disease ( 137 ), peripheral vascular disease ( 138 , 139 ), and production of anti-phospholipid antibodies ( 136 ). Moreover, smoking lowers the efficacy of medicines used to treat SLE ( 3 , 140 , 141 ). Likewise, a prospective cross-sectional study of Chinese SLE patients performed in 2015 reported that cigarette smoking causes the development and worsening of symptoms in SLE patients, including photosensitivity, nephropathy, proteinuria, compared with those in nonsmokers (after adjustment for age and gender), whereas SLEDAI scores were not significantly different in smokers and non-smokers ( 142 ).…”
Section: Effects Of Cigarette Smoking and Consumption Of Alcohol And ...mentioning
confidence: 99%
See 2 more Smart Citations
“…This likely leads to an acceleration of underlying and brewing autoimmunity, allowing it to manifest in SLE. These factors include current cigarette smoking, obesity (in particular, at younger ages), childhood and adult trauma, stress, posttraumatic stress disorder, low or no alcohol intake, environmental air pollution, environmental silica, and hormonal exposures and reproductive factors among women [reviewed in (58,119)]. While is it not known whether these environmental risk factors work via similar or disparate biologic pathways, nor whether they are perhaps also inextricably linked to other societal risk factors that are more difficult to measure, the picture of how and the extent to which they contribute to SLE susceptibility is coming into focus.…”
Section: Lifestyle and Environmental Risk Factors Related To Sle Risk...mentioning
confidence: 99%